Towards Automating the Personalization of Gamified Learning's Aesthetics: A Survey Comparing Themed and Standard Badges Generated by AI - Rodrigues, Luiz; Aranha, Renan Vinicius; Costa, Newarney T.; Ribeiro, Lucas de Almeida; Santos, Heder Filho S.; Pereira Júnior, Cleon X. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2024: Anais do XXXV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2024.244949, 2024)
Gamification has been effective in enhancing learning outcomes, though its impact varies due to individual learner differences, such as interests and personality traits. This paper presents a survey study (n = 107) examining opinions on themed versus standard badges automatically designed by Generative Artificial Intelligence (GAI), considering factors such as different themes, engagement with the theme, and personality traits. Preliminary results reveal that themed badges are generally more motivating than standard ones, regardless of the badge’s theme or the personality traits. These findings suggest that educators and designers can explore GAI to explore themed badges without being constrained by theme-specific effectiveness.